Use of Mobile Applications for Monitoring Adolescent Mental Health - Tri Budi Rahayu; Supriyanti Supriyanti; Jamila Kasim; Munazar Munazar; Arnes Yuli Vandika (Yayasan Adra Karima Hubbi, 2024)
Teenage mental health is becoming increasingly important in this modern era. However, the issue of accessibility to mental health services remains a significant obstacle. The use of mobile applications offers a potential solution to improve monitoring and intervention in adolescent mental health. This study aims to explore the effectiveness of using mobile applications in monitoring adolescents' mental health, as well as its impact on their quality of life. This study used a quantitative approach with a survey conducted on a sample of adolescents aged 13-18 years who used a mental health mobile application for six months. Data was collected regarding frequency of app use, changes in levels of anxiety and depression, and user perceptions of the app's benefits. The results of this study show that the use of mobile applications significantly reduces levels of anxiety and depression in adolescents. Additionally, users report improvements in emotion management skills and knowledge about mental health. The majority of respondents also felt comfortable and helped by the application features in managing daily stress. The conclusion of this study explains that using mobile applications for monitoring adolescent mental health has great potential to increase the accessibility and effectiveness of mental health services. This application can be an effective tool in providing support, education and intervention to teenagers in managing their mental health problems. Thus, the implementation of mobile applications in the context of adolescent mental health needs to be considered as part of a comprehensive strategy to improve adolescent well-being.